(untitled) (Research, Society and Development, 2022)
Occupational Therapy is a health profession that focuses on performing occupations to improve an individual’s functionality. Occupational therapy is currently entering the digital revolution, in which Rehabilitation Technologies (RT), such as robotics and virtual reality, are present in the practice of rehabilitation. The aim of the study was to characterize how Rehabilitation Technology is used in intervention by occupational therapists. A scope review was carried out in national and international occupational therapy journals, based on the Joanna Briggs Institute’s scope review guide, and the PRISMA-ScR checklist was also used for scope review. Twenty-eight articles were included and the results were analyzed quantitatively to generate graphs and tables, as well as inserted into a script for qualitative data collection. The results show that most occupational therapists use virtual reality as RT, and that it is more used in adult patients with Cerebral Vascular Accident (CVA), although RT can be used both in physical rehabilitation and in mental health, in patients of any age group. In addition to providing pleasurable moments in therapy, greater engagement and motivation, reducing therapist and patient fatigue, the use of RT presented therapeutic benefits, accuracy in assessments and gains in motor and functional skills.